Effect of Leadership, Discipline on Performance through Employee Motivation (International Journal of Scientific Research and Management (IJSRM), 2022)
This study aims to determine the relationship between leadership, work discipline on performance through employee motivation at PT. Distriversa Buanamas Makassar Branch. The data analysis method used is path analysis (path analysis). The object of research is all employees of PT Distriversa Buanamas Makassar Branch, totaling 30 people. The results showed that there was a positive and significant relationship between leadership on performance through employee motivation and there was a positive and significant influence between work discipline on performance through employee motivation. The results of this study found that leadership and work discipline were proven to increase employee performance by mediating the motivation variable. Therefore the company must be able to maintain and improve better leadership in order to support more optimal company operational activities and the organization must be able to pay attention to matters relating to employee work discipline so that employees are able to complete work on time in accordance with the expectations of the organization